Are myoepithelial cells confined to genital coelomic sinus in the gonads of sea stars?. (June 2022) - Kalachev, Alexander V.; Dyachuk, Vyacheslav A.
Highlights: Myoepithelial cells have been found in peritoneal epithelium of some species. Initially sea stars had myoepithelial cells in visceral peritoneal epithelium of the gonads. Some myoepithelial cells extend their processes across the genital coelomic sinus. Abstract: An ultrastructural study of the gonadal wall in 10 sea star species from the orders Forcipulatida, Paxillosida, Spinulosida, Valvatida and Velatida has shown variations in the presence of myoepithelial cells in the visceral peritoneal epithelium. These cells have only been found in the peritoneal epithelium of the gonads in Aphelasterias japonica (Forcipulatida: Asteriidae), Asterias amurensis (Forcipulatida: Asteriidae), Distolasterias nipon (Forcipulatida: Asteriidae), Diplopteraster multipes (Velatida: Pterasteridae), Luidia quinaria (Paxillosida: Ctenodiscidae), and Pteraster sp. (Velatida: Pterasteridae). Our results may shed light on the evolution of peritoneal epithelium of sea star gonads. It is probable that, initially sea stars had myoepithelial cells in visceral peritoneal epithelium of the gonads. The species from the orders Forcipulatida and Velatida have retained this plesiomorphic state, while many species from the orders Paxillosida, Spinulosida and Valvatida have lost myoepithelial cells from visceral peritoneal epithelium of their gonads.